NONCLASSICAL PROPERTIES OF TWO-MODE DISPLACED FOCK STATE - Ngoc Duy Tinh Phan; Thi Hong Thanh Le; Minh Duc Truong (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, we investigate a variety of nonclassical properties of a two-mode displaced Fock state (TMDFS). Nonclassical properties such as sum squeezing, difference squeezing, antibunching effect, and the Cauchy-Schwarz inequality will be discussed analytically for the TMDFS. The results show that by changing the Fock state parameters between modes and the displacement parameter, the TMDFS exhibits enhanced nonclassical behaviors and makes a valuable contribution to quantum optics.